Mengamati Perkembangan Anak Kelas 5 SD Melalui Observasi Kunjungan Ke Rumah - Ramadhan Lubis; Naila Sa’adah; Via Ivanka Br Sitepu; Dalila Sari Nasution; Nadya Azmi Lianka; Nadia Ivanka (CV. ITTC INDONESIA, 2025)
This study aims to examine the development of a 5th-grade elementary school student through the home visit approach involving direct interaction between the parent and the child. Home visits serve as an important means to gain an in-depth understanding of the child’s learning conditions, including family environment, social, and emotional factors that influence the developmental process and academic achievement. The research method used is qualitative, with data collected through observation, in-depth interviews with the parent and the child, and documentation of learning activities at home. The findings indicate that home visits can strengthen communication between the parent and the child, enhance learning motivation, and identify challenges and needs that are less visible within the school environment. Furthermore, the interactions during home visits enable the parent to provide more appropriate support tailored to the child’s condition and needs. In conclusion, home visits are an effective strategy to support the academic, social, and emotional development of a 5th-grade elementary student, and it is recommended that such visits be conducted regularly as part of efforts to improve learning quality and child development.